”En blomma behöver få känna solens strålar och vattna sin törst, för att inte torka ut” - Om internationella studenters sociala deltagande och ensamhet - Koskinen,Marcus (2025)
This study aims to examine the experience of international students from Lund and Malmö universities regarding social participation and loneliness throughout their studies abroad. I conducted qualitative interviews with international students from the universities. After I gathered my empirical data, I then assessed their experiences through Goffman’s stigma theory and Antonovsky’s sense of coherence theory. Results showed that the students had different ways of comprehending, managing, and finding meaning in social interactions while adapting to their new life in Sweden. Some of them also felt that they were stigmatized based on their background in some interactions.
Keywords: social work; international students; social participation; loneliness; sense of choerence; stigma; socialt arbete; internationella studenter; socialt deltagande; ensamhet; KASAM